33.9k views
5 votes
Solve for p: p - 6 = 5*
p = 1
p = 11
p = -1

User Karthiks
by
5.1k points

1 Answer

11 votes

Explanation:


\text{p - 6 = 5}

Since we want to get ' p ' on left hand side , remove the number ' - 6 '.


\text{p - 6 + 6 = 5 + 6} { The opposite of -6 is +6 and whatever we do to one side , we must do to the another side. So, I added 6 on both sides }


\text{p = 11} { On the left hand side , 6-6 = 0. That's how we removed the 6 so just 'p' is left. On the right hand side , 5+6 = 11 }

---------


\underline{ \underline{ \text{CHECK }}} :

Always check your answer by substituting your answer for the variable that you solved for. This guarantees you a right answer !


\text{p - 6 = 5}


\text{11 - 6 = 5}


\text{5 = 5}


\pink{ \underline{ \boxed{ \text{Our \: final \: answer : \boxed{ \underline{ \tt{p = 11}}}}}}}

Hope I helped ! ♡

Have a wonderful day / night ! ツ

▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁

User Yang Zhao
by
5.8k points